2015
DOI: 10.1111/jcmm.12738
|View full text |Cite
|
Sign up to set email alerts
|

The role of Card9 overexpression in peripheral blood mononuclear cells from patients with aseptic acute pancreatitis

Abstract: Activated mononuclear cells are an early event in the course of severe acute pancreatitis (SAP). To date, the molecular mechanism triggering peripheral blood mononuclear cells (PBMCs) is poorly understood. The aim of this paper was to determine the potential role of Card9 in SAP. We collected data from 72 subjects between January 2013 and June 2014. Subsequently, PBMCs were isolated on day 1, 3 and 5 of pancreatitis. Immunofluorescence staining, quantitative real‐time PCR, Western blotting, immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…This is therefore the first report to demonstrate that CARD9 expression is up-regulated in aseptic SAP and corresponds to previous findings [5]. In this study, it was found that CARD9 is overexpressed in SAP patients and was identified as a potential molecular marker due to its close correlation with the outcome and severity of pancreatic injury in SAP patients [5]. It has previously been shown that an up-regulation of CARD9 expression in SAP patients is associated with an upstream activation of the NF-jB and P38MAPK pathways [5].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is therefore the first report to demonstrate that CARD9 expression is up-regulated in aseptic SAP and corresponds to previous findings [5]. In this study, it was found that CARD9 is overexpressed in SAP patients and was identified as a potential molecular marker due to its close correlation with the outcome and severity of pancreatic injury in SAP patients [5]. It has previously been shown that an up-regulation of CARD9 expression in SAP patients is associated with an upstream activation of the NF-jB and P38MAPK pathways [5].…”
Section: Introductionsupporting
confidence: 91%
“…To the best of our knowledge, the early course of SAP is characterized by non‐infectious inflammation. This is therefore the first report to demonstrate that CARD9 expression is up‐regulated in aseptic SAP and corresponds to previous findings . In this study, it was found that CARD9 is overexpressed in SAP patients and was identified as a potential molecular marker due to its close correlation with the outcome and severity of pancreatic injury in SAP patients .…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Dysregulated CARD9 signaling has been implicated in autoimmune diseases of the eye,28 contact hypersensitivity,29 and aseptic acute pancreatitis 30. CARD9 is a strong therapeutic candidate for multiple reasons.…”
Section: Card9mentioning
confidence: 99%